Zoe Dumitrescu-Bușulenga și relațiile identitare ale imaginarului religios în opera lui Mihai Eminescu / ZOE DUMITRESCUBUȘULENGA AND THE IDENTITARY INTERFERENCES OF THE RELIGIOUS IMAGINARY IN MIHAI EMINESCU’S LITERARY WORK - Silviu Mihăilă (Incursiuni în imaginar)
Our research intends to answer to the question: was indeed Mihai Eminescu a religious poet or not? This question is a fragile topic that has become taboo in the filed of Romanian Literary Criticism. Over the years have been expressed many different and complex points of view that plunged Mihai Eminescu’s literary work in the arena of a triple interpretations. Zoe Dumitrescu-Bușulenga considers Mihai Eminescu to be a religious poet not only because he wrote sacred poetry (see poems like Rugăciune; Colinde, colinde; Învierea; Răsai asupra mea...a.s.o.), but also many biographical aspects that are well known reinforced this idea. In the same time, Zoe Dumitrescu-Bușulenga circumscribes the religious imaginary of Mihai Eminescu’s literary work according to the triple nuance of the creative language that Northrop Frye develops in The Great Code. The Bible and The Literature. These three critical interpretations are: an exclusively Romantic poet (Eminescu belongs to the Romantic paradigm, he defines himself being a Romantic writer in Eu nu cred nici în Iehova), an atheist poet (Eminescu has been read in an atheist reading grid by the proletcult/ communist doctrine) and, last but not least, a religious poet. Therefore, our critical essay focuses exactly on the poet’s religious identity construction and de-construction as it is perceived in connection with his poetical imaginary poliedrically reflected.